PENGARUH ALIRAN REMBESAN DAN KEMIRINGAN LERENG TERHADAP PRILAKU KEGAGALAN LERENG - Nofrizal Nofrizal; Amelia Sulastri; Febi Silvia Deni (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2020)
The effect of water flow or seepage into the soil will affect the stability of the slope. For this reason, it is necessary to study the slope collapse with variations in the slope. The 3-dimensional spring model is made in the form of a frame with a size of 100 cm long x 70 cm high x 7 cm wide. The slope model is made from sand with a slope of 30o, 40o and 60o. The soil shear strength test is also carried out on samples of soil that has collapsed with different water content. In general, the shear strength of the soil has decreased due to water seepage. Slope failure with a slope of less than 40o only occurs at the foot of the slope, while slopes with a slope greater than or equal to 40o experience collapse along the slope height to the top of the slope.